Comparations Of Glycated Albumin Among Type 2 Diabetes Mellitus Patient With Normoalbuminuria, Microalbuminuria And Macroalbuminuria - Raja Iqbal Mulya Harahap; Nina Tristina; Ruri Rizki Anriani (Fakultas Kedokteran Universitas Riau, 2023)
Diabetic nephropathy is the most often complication of diabetes mellitus (DM). Complications of diabetic nephropathy can occur through several pathways, one of which is the formation of Advanced Glycation End Products (AGEs) through the formation of Glycated Albumin (GA). Glycated albumin (GA) is a medium-term glycemic control (2-3 weeks), shorter duration than HbA1c (2-3 months). The aim of this study was to compare the levels of GA in T2DM patients with normoalbuminuria, microalbuminuria, and macroalbuminuria. This is a cross-sectional study with subjects were 105 outpatients who had been diagnosed with T2DM by clinicians at Hasan Sadikin Hospital’s Endocrinology Clinic. We examined urinary albumin per Creatinine (u-ACR) and blood GA Increased GA level was found in 75.24% subjects. Kruskal Wallis test in GA serum levels of patients with T2DM normoalbuminuria group, microalbuminuria and macroalbuminuria revealed statistically significant (p <0.001), with median and range of GA in normoalbuminuria 15,9% (12,1-21,89)%; microalbuminuria 20,9% (12,9-47,2)%; dan macroalbuminuria 23,1% (13,6-46,1)%. Statistical analysis showed that the GA serum level was significantly different between T2DM patients with normoalbuminuria and macroalbuminuria, but not between those with microalbuminuria and macroalbuminuria (p=0.001 and p=0.137, respectively). The result showed that the extensive kidney damage at the subject, the higher result of Glycated Albumin level in serum.